La televisión y los formatos educativos en Ecuador - Mora Tomalá, Alejandra Nathaly (2019)
Television should focus on increasing the audience to educational programs that are transmitted through television. We must bear in mind that television is a means of communication that has positive content, as negative, but it is very important that children and young people; they are interested in benefiting their intellectual development. Based on everything raised in this paper, it can be established that television has a great influence on the development of society, and that is why the formation of educational and cultural content should favor educational education incorporating creative audiovisual content that educate and enable learning from: the environment, tourism, science, technology, etc. That is why the EDUCA program is a new educational scenario that contributes to the learning of values and knowledge to build a society of good living.